Turbulent heat transfer in a microfin tube with twisted tape insert - Eiamsa-Ard, Smith; Kongkaitpaiboon, Vichan; Eiamsa-Ard, Petpices; Pimsarn, Monsak (My University, 2012)
The purpose of the present study is to investigate experimentally the heat transfer, turbulent flow friction and thermal performance factor characteristics in a microfin tube with a twisted tape insert. In the experiment, heat transfer augmentation is expected from both the turbulence of flow near the tube wall produced by fin surface and the swirling flow generated by the twisted tape. Effect of the twisted tape at different twist ratios of y/W = 3, 4 and 5 on the heat transfer enhancement characteristics is also reported. In the experimental set-up, cold water was passed through the uniform heat flux tube in a range of Reynolds number between 5000 and 17000. The experimental results obtained are compared with those from plain tubes. The results show that the thermal performance from using the microfin tube fitted with twisted tape is considerably higher than that from the microfin tube alone. The Nusselt numbers and friction factors are found to be, respectively, 3.0, 4.0 and 5.0 times over the microfin tube alone for the microfin tube combined with twisted tape. In addition, the results demonstrate that as the twist ratio (y/W) decreases, the twisted tape will give better heat transfer enhancement. The microfin tube combined with twisted tape provides higher thermal performance factor than those the microfin tube alone around 172%, 142% and 124%, respectively, for y/W = 3, 4 and 5. The results were correlated in the form of Nusselt number as a function of Reynolds number, Prandtl number and twist ratio.
Keywords: Heat exchanger; Heat transfer; Microfin tube; Swirl flow; Turbulent flow; Twisted tape